Gambaran Hasil Pemeriksaan Sgot Dan Sgpt Pada Penghirup Lem Di Jalan Abdul Kadir Kota Makassar - Hasni Hasni; Jurnal Syarif; Isnawaty Darwis (Jurnal Media Laboran, 2018)
This research has the background of glue inhaler, inhaled glue is aibon glue or Fox glue which contains Lysergic Acid Diethyilamide (LSD) which is inserted into the human body inhaled through the nose that can change a person's mind, mood, or feeling, and behavior. Continuous use will result in physical and / or psychological dependence. The risk that is certain to occur is damage to the nervous system and other important organs such as the liver, lungs and heart. This study aims to describe the results of the examination of SGOT and SGPT levels in glue inhalers and the benefits of this research are as information material for the public about the importance of knowing adverse effects of glue inhalers. This type of research is descriptive laboratory observation by examining SGOT and SGPT levels on glue inhalers using a photometer. From the results of the examination on 10 glue inhaler samples at Jalan Abdul Kadir, Makassar City, there was no increase in SGOT and SGPT levels with the sample code A = (GOT: 7.19 U / l) (GPT: 34.27 U / l), Sample B = (GOT: 18.74 U / l) (GPT: 27.73 U / l), Sample C = (GOT: 23.42 U / l) (GPT: 39.57 U / l), Sample D = ( GOT: 22.22 U / l) (GPT: 27.00 U / l), Sample E = (GOT: 32.10 U / l) (GPT: 33.36 U / l), Sample F = (GOT: 27.51 U / l) (GPT: 37.89 U / l), Sample G = (GOT: 29.78 U / l) (GPT: 40.00 U / l), Sample H = (GOT: 35, 00 U / l) (GPT: 40.54 U / l), Sample I = (GOT: 31.17 U / l) (GPT: 39.71 U / l) and Sample J = (GOT: 36.81 U / l) (GPT: 36.82 U / l).